Donggo Kala People’s Resistance Against the Dutch Government in Bima 1907-1910 - Sukarddin, Sukarddin; Suryaningsih, Lili (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
The aim of this research is to find out more about the existence of foreign interference in the life of a society, in this case the interference of the Dutch in the government system of the Bima Sultanate. The research method used is the historical method which includes heuristics (data collection), source criticism, interpretation (interpretation), and historiography (historical writing). The results of the research show that the background to the resistance of the Donggo Kala people was caused by the Dutch starting to exercise political domination, economic exploitation and cultural penetration with the aim being that the Dutch could gain as much profit as possible through collecting various kinds of taxes and employing forced labor. The Donggo Kala people were in the grip of the Dutch colonialists and experienced physical and spiritual torture, resulting in the enthusiasm of the Donggo Kala people to fight against the Dutch. However, the resistance of the Donggo people had a very big impact on both parties, namely the impact that occurred between the Dutch people and the Donggo Kala people. For the leader of Donggo Kala, namely, officially Donggo fell into Dutch hands, while for the Dutch, with the Donggo Kala people's resistance won, the Indies government The Dutch could control directly the entire territory of the Bima Sultanate.